COMPREHENSIVE REVIEW OF AORTIC ARCH ANEURYSM MANAGEMENT: FROM PATHOPHYSIOLOGY TO ADVANCED SURGICAL TECHNIQUES - Rafał Kuśmider,; Małgorzata Leśnik,; Hubert Kostka,; Damian Dolata,; Adrian Zagórski,; Patrycja Wierzbowska,; Jadwiga Kleinrok,; Anna Bereta-Kostaś, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Aortic arch aneurysm is a rare life threatening condition; with in-hospital mortality of 50% following their rupture it is imperative that patients are informed by their medical providers of the risk factors, and available treatments. The purpose of this literature review is to provide an overview of possible surgical interventions, pathophysiology, and presentation of aortic arch aneurysms.Description of the state of knowledge: With prevalence at just 0.16 - 0.34% aneurysms of the thoracic aorta are less common than those located within the abdominal aorta. Of those located in the thorax only 10% locate within the aortic arch. Genetic disorders such as Loeys-Deitz syndrome, Marfan syndrome, and bicuspid aortic valve, as well as non-genetic factors such as hypertension, inflammatory cell infiltration of the aortic wall, and SMC phenotype switching can all be linked with aortic arch aneurysm onset and progression. The clinical presentation of this aortic pathology is often scarce, however progressive enlargement of the aneurysmal sack may in time cause symptoms stemming from compression of neighboring structures. Surgical techniques used in aortic arch aneurysm management range from very invasive procedures requiring cardio-pulmonary bypass and deep hypothermia, to minimally invasive, fully endovascular approaches, with hybrid procedures situated between them.Conclusions: Ongoing advancements in imaging techniques and relentless innovation in the field of vascular surgery continue to bring new, less invasive aortic arch aneurysm treatment options. As the surgical repertoire expands, more patients - previously deemed not suitable for intervention - are able to take advantage of the life saving aortic arch repair.